1993
DOI: 10.1523/jneurosci.13-06-02323.1993
|View full text |Cite
|
Sign up to set email alerts
|

Patch-clamp analysis of spontaneous synaptic currents in supraoptic neuroendocrine cells of the rat hypothalamus

Abstract: Spontaneous synaptic currents were recorded in supraoptic magnocellular neurosecretory cells using whole-cell patch-clamp techniques in the rat hypothalamic slice preparation. Numerous spontaneous excitatory and inhibitory postsynaptic currents (EPSCs and IPSCs) were observed in the 27 cells recorded. The rate of occurrence of the spontaneous currents and the relative proportion of EPSCs versus IPSCs varied significantly from cell to cell. Miniature EPSCs and IPSCs were clearly distinguished from background no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
100
0
2

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(110 citation statements)
references
References 31 publications
8
100
0
2
Order By: Relevance
“…Synchronous firing of magnocellular neurons in the supraoptic nucleus (SON) and the paraventricular nucleus triggers oxytocin release. The spiking frequency of these neurons is under control of a GABAergic input (1)(2)(3). The postsynaptic ␥-aminobutyric acid type A (GABA A ) receptors that mediate this input are susceptible to allosteric interaction with the neurosteroid allopregnanolone 3␣-OH-DHP during some stages of the female reproductive cycle, in particularly during pregnancy (4,5).…”
mentioning
confidence: 99%
“…Synchronous firing of magnocellular neurons in the supraoptic nucleus (SON) and the paraventricular nucleus triggers oxytocin release. The spiking frequency of these neurons is under control of a GABAergic input (1)(2)(3). The postsynaptic ␥-aminobutyric acid type A (GABA A ) receptors that mediate this input are susceptible to allosteric interaction with the neurosteroid allopregnanolone 3␣-OH-DHP during some stages of the female reproductive cycle, in particularly during pregnancy (4,5).…”
mentioning
confidence: 99%
“…The release of the two hormones is closely related to the electrical activity of the magnocellular neurones, which is known to be modulated by various neurotransmitters and neuromodulators (for recent reviews, see Hatton, 1990; Armstrong, 1995; Leng et al 1999). The site of modulation is thought to be mainly at the soma or dendrites, aiid fast synaptic inputs via ionotropic GABA and glutamate receptors play major roles in this modulation (Wuarin & Dudek, 1993).It has been reported that GABA and glutamate are present in approximately 50% and 30%, respectively, of the total presynaptic neurones in the region of the supraoptic nucleus (Meeker et al 1993) and that spontaneous excitatory and inhibitory postsynaptic currents (EPSCs and IPSCs) in supraoptic neurones directly reflect the spontaneous release of glutamate and GABA from the terminals of presynaptic neurones at the supraoptic nucleus (Wuarin & Dudek, 1993; Kabashima et al 1997). Many different types of receptors are present at presynaptic sites in the supraoptic nucleus, but whether or not the ligands that activate these receptors influence the release of the two major neurotransmitters remains to be elucidated.…”
mentioning
confidence: 99%
“…The release of the two hormones is closely related to the electrical activity of the magnocellular neurones, which is known to be modulated by various neurotransmitters and neuromodulators (for recent reviews, see Hatton, 1990; Armstrong, 1995; Leng et al 1999). The site of modulation is thought to be mainly at the soma or dendrites, aiid fast synaptic inputs via ionotropic GABA and glutamate receptors play major roles in this modulation (Wuarin & Dudek, 1993).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…1983) and in vitro (Randle & Renaud, 1987). Furthermore, all spontaneous inhibitory postsynaptic potentials in supraoptic neurones in vitro are GABA mediated (Randle et al 1986;Wuarin & Dudek, 1993). The important role of GABA in control of VP and OT neuronal activity suggested by anatomical and electrophysiological evidence has been further supported by functional studies.…”
Section: MD Brown School Of Sport and Exercise Sciences University Omentioning
confidence: 99%